Multimodalitas pada Video Klip Lagu “Gala Bunga Matahari” Karya Sal Priadi - Siti Nuraini; M. Bayu Firmansyah; Ilmiyatur Rosidah (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to reveal the meaning formed through the interaction of various forms, namely language, images, music, sound, and movement in the song video clip. Using a qualitative method with a multimodal discourse analysis approach, this study analyzes how the five forms of modes work simultaneously in conveying messages. The results of the study show that each form plays an important role in building the theme of longing, loss, and hope. Language is used to convey the narrative, images and movements strengthen the emotional meaning, while music and sound create an atmosphere that supports the overall message. These findings indicate that the multimodal discourse approach is able to reveal complex meanings in works of art, as well as being a means to represent ideas, experiences, and social realities through various complementary forms.